SCREENING AND EARLY DETECTION OF LUNG CANCER: A COMPREHENSIVE SYSTEMATIC REVIEW - Agustin Arifah Y, Nurhidayati; Yudistiro, Fadhiel (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Lung cancer is the second most commonly diagnosed cancer and the leading cause of cancer-related deaths globally, accounting for the greatest economic and public health burden of all cancers. In 2020, lung cancer accounted for approximately 2.2 million cases and nearly 1.8 million deaths worldwide. The aim: The aim of this study to show about screening and early detection of lung cancer. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: Four publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Early screening and diagnostic methods of lung cancer, x-ray screening is not recommended. LDCT has obvious advantages and is the most promising imaging method in early screening of lung cancer.